1982
DOI: 10.1007/bf02376797
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil gas contamination on tree root growth

Abstract: Summary Rooted-cuttings and saplings of green ash (Fraxinus lanceolata) and hybrid poplar (Populus spp) were planted on a former municipal refuse landfill and on a nearby nonlandfill control plot. The root systems of four trees of each species and size were excavated on the landfill plot -two growing in an area where the concentrations of anaerobic landfill gases were relatively high and two in a relatively low-gas area. Two trees of each species and size were also excavated on the control. The root systems of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 2 publications
4
29
1
Order By: Relevance
“…Vegetation damage at or nearby to such sites is well documented in the literature Leone et al, 1977;Leone and Flower, 1982;Gilman, 1980;Gilman et al, 1981Gilman et al, , 1982Gilman et al, , 1985Arthur et al, 1985). The damage occurs primarily due to oxygen deficiency in the root zone resulting from a direct displacement of oxygen by landfill gas.…”
Section:  mentioning
confidence: 91%
“…Vegetation damage at or nearby to such sites is well documented in the literature Leone et al, 1977;Leone and Flower, 1982;Gilman, 1980;Gilman et al, 1981Gilman et al, , 1982Gilman et al, , 1985Arthur et al, 1985). The damage occurs primarily due to oxygen deficiency in the root zone resulting from a direct displacement of oxygen by landfill gas.…”
Section:  mentioning
confidence: 91%
“…Methane oxidising activity, with a decrease in soil O 2 and an increase in soil biomass, has been demonstrated around leaks in natural gas pipes (Adams and Ellis, 1960;Adamse et al, 1972). Arthur et al (1985), Gilman et al (1982) and Hoeks (1972b) found that elevated CH 4 concentrations were associated with depleted O 2 of between 0 and 12% and elevated CO 2 concentrations of up to 35% in the soil atmosphere.…”
Section: Effect Of Bacterial Oxidationmentioning
confidence: 95%
“…Methane per se has not been shown to be toxic to plants, and aerial contact of plants with natural gas has not been shown to have any harmful effects- Gustafson (1944) found that a range of species showed no signs of altered growth or epinasty (a change in the angle between the petiole and the stem) when exposed to concentrations of 2% CH 4 in air for up to 21 days. It has been suggested that the main damaging effect on plant growth of natural gas leaking from pipelines into the soil is due to the displacement of soil O 2 (Arthur et al, 1985;Gilman et al, 1982;Hoeks, 1972b;Smith, 2002) and this effect may be compounded by the oxidation of leaking CH 4 by methanotrophic bacteria that utilise the CH 4 present in natural gas as a carbon-based energy source (Hanson and Hanson, 1996). However, Meissner et al (1999) suggest that the effect may be more complicated than simple displacement of O 2 by the CH 4 .…”
Section: Introductionmentioning
confidence: 98%
“…A lot of studies on landfills can be found in the literature -about root contamination by gas (Gilman et al, 1982), methane production (Themelis and Ulloa, 2007), microbiological studies (Boeckx et al, 1996) and ecological performance after the restoration of plant and animal communities Wong et al, 2015) -but nothing can be found about hydrological properties of cover soil in relation to plant coverage.…”
Section: Cassinari Et Al: Hydraulic Properties and Plant Coveragementioning
confidence: 99%